2000
DOI: 10.1016/s0168-6496(00)00077-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection and distribution of insertion sequence 1 (IS1)-containing bacteria in the freshwater environment

Abstract: The distribution of insertion sequence 1 (IS1)-containing bacteria was investigated in Windermere (Cumbria, UK), a freshwater body impacted by treated sewage discharge and run-off from the surrounding catchment. Culturable IS1-containing bacteria were recovered from the water column at three depths in Windermere North Basin (WNB) and South Basin (WSB), and from sediment at both sites (at the sediment surface in WSB and to a depth of 12^13 cm in WNB). Polymerase chain reaction amplification of IS1 and the Esche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 30 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Soil, water, sediment, and perhaps food are other habitats of E. coli, and the bacterium might spend comparable times in each of its two main habitats (88,281). While pollution from human sources may be the most important source of E. coli in the environment (29,260), the fact that this bacterium was found in pristine tropical waters, where it remained physiologically active and grew at rates dependent on nutrient levels, suggests that it can be a natural inhabitant in these environments and that it may be part of a previously established community (22). E. coli can also replicate and survive in soil protozoa.…”
Section: The Two Habitats Of E Colimentioning
confidence: 99%
“…Soil, water, sediment, and perhaps food are other habitats of E. coli, and the bacterium might spend comparable times in each of its two main habitats (88,281). While pollution from human sources may be the most important source of E. coli in the environment (29,260), the fact that this bacterium was found in pristine tropical waters, where it remained physiologically active and grew at rates dependent on nutrient levels, suggests that it can be a natural inhabitant in these environments and that it may be part of a previously established community (22). E. coli can also replicate and survive in soil protozoa.…”
Section: The Two Habitats Of E Colimentioning
confidence: 99%
“…IS 1 (SB) and IS 1 (SS), and the nucleotide sequences of IS 1 (SD) and IS 1 (SF) in Shigella dysenteriae and Shigella flexneri , respectively, have been reported (Ohtsubo et al , 1981, 1984; Hsu & Chen, 2003; Yang et al , 2005). These IS 1 sequences and nucleotide sequences of IS 1 elements in other bacterial species, including Citrobacter freundii , Enterobacter aerogenes , Enterobacter cloacae , Escherichia coli , Escherichia fergusonii , Eschreichia hermannii , Escherichia vulneris , as well as an unknown bacterial species in sediment, were compiled (Ohtsubo et al , 1981, 1984; Umeda & Ohtsubo, 1991; Lawrence et al , 1992; Rhodes et al , 2000; Perna et al , 2001; Hsu & Chen, 2003), and PCR primer pairs specific for Shigella sonnei were designed. Figure 1 shows the sequences of one such IS 1 primer pair, IS1SS and IS1SR3, which are identical to 250–265 and 618–603 bp of IS 1 (SS) in Shigella sonnei (Ohtsubo et al , 1984).…”
Section: Resultsmentioning
confidence: 99%
“…The 33 Shigella sonnei isolates included 28 Shigella sonnei isolates recovered from patients in southern, northern, central and eastern Taiwan, and five Shigella sonnei ATCC strains, while the 72 non‐ Shigella sonnei isolates included eight bacteria that had been previously recovered from ground‐water samples and identified in the laboratory of this study and the bacteria reported to contain IS 1 sequences, i.e. Citrobacter freundii , Enterobacter aerogenes , Enterobacter cloacae , Escherichia coli , Escherichia fergusonii , Escherichia hermannii , Escherichia vulneris , Klebsiella pneumoniae , Salmonella typhimurium, Serratia marcescens , Shigella dysenteriae , Shigella boydii and Shigella flexneri (Nyman et al , 1981; Ohtsubo et al , 1984; Bustos‐Martinez & Gomez‐Eichelmann, 1987; Umeda & Ohtsubo, 1991; Lawrence et al , 1992; Matsutani & Ohtsubo, 1993; Rhodes et al , 2000; Hsu & Chen, 2003). Characteristics of these isolates are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations